2022
DOI: 10.3390/ijerph191912470
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic: Impact on Cancer Patients

Abstract: In December 2019, there were first reports of an atypical pneumonia detected in Wuhan city, China [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…AAMR in patients with cancer and COVID‐19 were found to be significantly higher in NH Black or African American, Hispanic or Latino, and NH American Indian or Alaskan Native groups in 2020, exacerbating persistent disparities in health outcomes in these groups in the US. This goes in line with known findings which showed that cancer‐associated COVID‐19 mortality was higher in Black and Hispanic groups compared to NH White and NH Asian groups 3 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…AAMR in patients with cancer and COVID‐19 were found to be significantly higher in NH Black or African American, Hispanic or Latino, and NH American Indian or Alaskan Native groups in 2020, exacerbating persistent disparities in health outcomes in these groups in the US. This goes in line with known findings which showed that cancer‐associated COVID‐19 mortality was higher in Black and Hispanic groups compared to NH White and NH Asian groups 3 …”
Section: Discussionsupporting
confidence: 92%
“…
Persons with cancer have significantly higher risk of adverse outcomes and mortality due to Inherent in this relationship are associations with underlying risk factors including higher burden of comorbidities, older age, immunosuppression due to chemoimmunotherapy use, and need for more frequent clinical visits for follow-up appointments and treatments. [1][2][3] In addition, patients with cancer during the pandemic experienced more problems with access to care due to a variety of reasons, such as difficulty in obtaining timely appointments due to the healthcare shifts in focusing on COVID-19 specific care, leading to potential delayed diagnosis and treatments. 4 Sociodemographic factors such as zip code of residency, non-Hispanic (NH) Black race/ethnicity, and male sex have also been associated with hospitalization and mortality, however, their study has been limited in the pandemic.
…”
mentioning
confidence: 99%
“…29 Even after lockdowns were lifted, patients choose not to come to clinics or hospitals for cancer screening and treatment due to fears of catching the virus. 30,31 There were reductions in the number of cancer surgeries, delays in radiotherapy and chemotherapy, as well as reductions in supply chains that were crucial for surgical equipment. [29][30][31][32] In India, in one hospital system in New Delhi, there was a 33.7% reduction in major cancer surgeries in 2020.…”
Section: Impact Of the Covid-19 Pandemic And Delays In Cancer Surgica...mentioning
confidence: 99%
“…30,31 There were reductions in the number of cancer surgeries, delays in radiotherapy and chemotherapy, as well as reductions in supply chains that were crucial for surgical equipment. [29][30][31][32] In India, in one hospital system in New Delhi, there was a 33.7% reduction in major cancer surgeries in 2020. 33 Unlike some other diseases, delays in cancer screening can lead to advanced disease at presentation, which can necessitate more complex surgical procedures that are associated with poor outcomes.…”
Section: Impact Of the Covid-19 Pandemic And Delays In Cancer Surgica...mentioning
confidence: 99%
See 1 more Smart Citation